The interaction of polyacid-modified composite resins ("compomers") with aqueous fluoride solutions (Journal of Applied Oral Science, 2009)
OBJECTIVE : The aim of this study was to investigate how the release of fluoride from two compomers and a fluoridated composite resin was affected by exposure to KF solution. MATERIAL AND METHODS: Two compomers (Dyract AP and Compoglass F) and one fluoridated composite (Wave) were prepared as discs (6 mm diameter and 2 mm thick), curing with a standard dental lamp. They were then stored in either water or 0.5% KF for 1 week, followed by placement in water for periods of 1 week up to 5 weeks total. Fluoride was determined with and without TISAB (to allow complexed and decomplexed fluoride to be determined), and other ion release (Na, Ca, Al, Si, P) was determined by ICP-OES. RESULTS: Specimens were found not to take up fluoride from 100 ppm KF solution in 24 h, but to release additional fluoride when stored for up to five weeks. Compomers released more fluoride cumulatively following exposure to KF solution (p